2006
DOI: 10.1007/s10555-006-8502-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical patterns of metastasis

Abstract: In human solid cancer, lymph node status is the most important indicator for clinical outcome. Recent developments in the sentinel lymph node concept and technology have resulted in a more precise way of examining micrometastasis in the sentinel lymph node and the role of lymphovascular system in the facilitation of cancer metastasis. Different patterns of metastasis are described with respect to different types of solid cancer. Expect perhaps for papillary carcinoma and sarcoma, the overwhelming evidence is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 110 publications
1
84
0
Order By: Relevance
“…Blindending lymphatic capillaries drain fluid, cells, and macromolecules from tissue interstitium into a hierarchy of vessels punctuated by lymph nodes (LN), which provide immunologic surveillance for a particular lymphatic drainage basin (3). The presence of metastatic tumor cells in the "sentinel" LN draining a tumor site is a key factor in disease management: substantial clinical data indicates adverse prognostic significance of tumor-positive LNs for many tumor types (4,5). However, a clear understanding of the mechanistic role of LNs in tumor progression is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Blindending lymphatic capillaries drain fluid, cells, and macromolecules from tissue interstitium into a hierarchy of vessels punctuated by lymph nodes (LN), which provide immunologic surveillance for a particular lymphatic drainage basin (3). The presence of metastatic tumor cells in the "sentinel" LN draining a tumor site is a key factor in disease management: substantial clinical data indicates adverse prognostic significance of tumor-positive LNs for many tumor types (4,5). However, a clear understanding of the mechanistic role of LNs in tumor progression is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although malignant cancers can spread to a wide variety of body tissues, only a few tissues, such as lymph nodes, bone, liver and lung, offer favorable conditions for metastasized cancer cell survival [4] . It has recently been suggested that the chemokine and chemokine receptor family [1] play a significant role in this organ tropism.…”
Section: Introductionmentioning
confidence: 99%
“…PET together with CT images showed a 15% increase in the accurate identification of nodal staging over using the PET images alone (Jeong, et al, 2007). PET/CT seems to have a higher sensitivity and specificity for detecting lymph node metastasis (Leong, et al, 2006, Wild, et al, 2006.…”
Section: Positron Emssion Tomography (Pet)mentioning
confidence: 93%